Periprosthetic Knee Infection Caused by Candida glabrata: A case report and literature review - Sakdinakiattikoon, MD, Manoon; Tanavalee, MD, Aree (Journal of Southeast Asian Orthopaedics, 2022)
Infection following total knee arthroplasty (TKA) is a serious complication that can cause devastating consequences. The treatment of this condition involves economic and social burden(1-2). A wide variety of pathogens are known to cause periprosthetic knee infection. The majority of infections are caused by gram-positive bacteria, of which, Staphylococcus aureus and Staphylococcus epidermidis infections occur most often(3-4). Fungal periprosthetic knee infection is uncommon. This condition represents a therapeutic challenge because clear treatment guidelines have not yet been established. We presented a case of Candida glabrata infection following TKA which successfully managed with two-stage exchange arthroplasty.